Infrared based technology to determine strength of concrete - Fasya Rafiqa, Saice (2019)
Infrared Thermography is an alternative tool to measure concrete strength apart of using compressive machine method. This study is about developing a Non-Destructive method using infrared-based technology to measure the strength of concrete in order to preserve the structure’s surface. Infrared Thermography is a technology that becomes well-known in the Civil Engineering field due to its non-contact characteristics. It allowed users to detect change of temperature on an object surfaces. The objectives of this study are to develop a non-destructive testing method that able to detect high strength concrete by using infrared technology and to determine the correlation of infrared thermography, strength, and porosity of the concrete. This method will be a positive impact to civil engineering and architectural field as the method promote an aesthetics finishing to determine concrete strength without having to crush the concrete. This method started by producing different concrete grade (Grade 30, Grade 35, Grade 40, Grade 45, Grade 50, Grade 55 and Grade 60) with size 150mm x 150mm x 150mm to be experimented using the Non-Destructive Testing (NDT) and Destructive Testing (DT). The infrared thermal images sampling was done on Day 7 and Day 28 of concrete curing. There are 3 thermal images taken from 2 surface of concrete cubes for each grade of concrete. The step afterward was to convert the thermal images into contour plot image using MATLAB software and then the contour plot will be analysed using AutoCAD by selecting the 3-point circle function to determine the diameter of each thermal colour on the infrared images. There are 3 main thermal colour focus in this study which are White. Yellow, and, Orange. The white thermal colour indicate the highest temperature among the other two thermal colour since the heat was applied directly on to that area before spread to the yellow and orange area. The DT were done right after the NDT process. The analysis of result is continued by finding out the lower, middle, and upper limit of yellow and orange thermal colour. However, since the white thermal colour is at the middle of the infrared images, it only had the upper limit only. The result shown that the most reliable thermal colour that have the highest correlation between the diameter of thermal colours and concrete grade is the white thermal colour with an R2 value of 0.9877. While for the correlation between the diameter of thermal colours and porosity of concrete, the white thermal colour show the lowest correlation with an R2 value of 0.7673. This is due to when an object is in high temperature state, the particles of the object move faster, thus no matter how porous the concrete is, the result will be less effective. Compare to the yellow and orange thermal colour, the temperatures start to spread across the concrete surface and the particle movement start to stabilize. Since the orange thermal colour is the most in the most outer side, it shows the highest R2 value. The result from AutoCAD then gather and analyse to find the correlation between the concrete grade, porosity, and the diameter of the contour plot. The correlation between the three of them are acceptable and the objectives are considered achieved. The analysis of result show that higher concrete grade, is in a less porous state, means it is denser, and transfer the heat faster on a concrete surface, thus making the diameter of each thermal colour bigger on the infrared images.